PENGARUH PEMBERIAN PAKAN KONSENTRAT DAN UREA MOLASES BLOK (UMB) TERHADAP HEMATOKRIT SAPI POTONG - Jumriah Syam, Jumriah Syam; Tolleng, A L; Umar, Umar (Jurnal Ilmu dan Industri Peternakan, 2017)
This study aims to find out how the effect of feed concentrate and the urea molasses block (UMB) of the hematocrit value of beef cattle. Research conducted at the Samata Integrated Farming System (FIS) Gowa Distric, and Lab Animal Physiology Faculty of Animal Husbandry, Hasanuddin University, Makassar. The method used a randomized desain (RAK) with a pattern of 2 x 6, (T1; forage 70 % + concentrate 30%), (T2; forage 70 %v+ UMB 30%), using 12 male bali cattle in the range of age of 1.5 - 2 years. Data analysis using T-student. The results showed that feeding concentrates and urea molasses block (UMB) was not significant (P> 0.05) to the hematocrit value of beef cattle